THE INFLUENCE OF FIGURATIVE DEVICES IN CHILDREN’S LITERATURE ON STUDENTS’ AESTHETIC TASTE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article provides a scientific-theoretical analysis of the role of figurative devices used in children’s literature in shaping the aesthetic taste of primary school students. The study examines the impact of artistic devices such as epithet, metaphor, personification, and comparison on the development of students’ imagination, emotional perception, artistic thinking, and sense of beauty. Literary analysis, observation, and pedagogical experiment methods were used during the research. The results show that the purposeful use of figurative devices enhances the effectiveness of aesthetic education in primary school learning processes.